Christian building patronage in the cities of late antique and Merovingian Gaul, c. 300–751 - Lewis, J (2021)
This is the first systematic investigation of the explosion in Christian building projects that transformed the cities of Gaul between the fourth and eighth centuries CE. Despite the disruption and simplification of society that accompanied the dissolution of Roman rule in this period, in many cases the extent and variety of such activity far surpassed what would have been necessary to endow Gallic cities with the essential Christian amenities. This study approaches this phenomenon through the lens of patronage, and in doing so addresses current debates regarding late antique urbanism, the chronology and pace of Christianisation, elite behaviour, the extent of episcopal power, and the nature of ‘barbarian’ kingship. It begins by sketching the parameters of urban and suburban Christian building patronage, acknowledging that while they intersected at times, four broad building categories can be distinguished: episcopal groups, the cult of saints, monasticism, and pastoral care. Through a series of case studies that illuminate the results of a broader quantitative analysis, this framework is then used to explore the motivations of the different patron groups who sponsored this building. Chapter three considers Gaul’s ecclesiastics and especially its bishops, chapter four the laity, and chapter five the region’s ruling families. Chapter six then examines the practice in the round, highlighting a number of overarching patterns of patronage across time, space, and patron group. While recognising that the prospect of divine intercession attracted donors at all social levels, this study emphasizes how urban and suburban Christian building patronage was a central component of elite competition in this period. The apparent rise and fall in the practice’s intensity thus reflects the response of the upper echelons of Gallic society to the evolving political and ideological significance of the region’s cities during the transition from late antiquity to the middle ages.